Missing, Presumed Trafficked: Towards non-binary understandings of ‘wayward’ youth in Jamaica - Sanchez Taylor, Jacqueline; O'Connell Davidson, Julia (Anti-Trafficking Review, 2022)
Boys and LGBTQ youth, especially those who go missing from home, have recently started to appear in mainstream anti-trafficking discourse as a group of children who are peculiarly vulnerable to human trafficking. This paper reports findings from research with Jamaicans who experienced various forms of violence and exploitation as children. Our data is consistent with the claim that boys and LGBTQ Jamaicans are amongst those who experience forms of violence and exploitation that policy makers often discuss under the heading ‘sex trafficking’. However, the same data also challenges the conceptual binaries used to frame assumptions about ‘sex trafficking’ as a significant threat to Jamaican youth and informs assumptions about missing children as victims of trafficking. In this way, the paper provides empirical support for criticisms of the turn towards including boys and LGBTQ youth as victims of ‘sex trafficking’, and of dominant discourse on ‘child trafficking’ more generally.